Health care professionals' adherence to partograph use in Ethiopia: analysis of 2016 national emergency obstetric and newborn care survey - Solomon Weldemariam Gebrehiwot; Mulugeta Woldu Abrha; Haftom Gebrehiwot Weldearegay (BMC, 2020)
Abstract Background The period around childbirth and the first 24 hours postpartum remains a perilous time for both mother and newborn. Health care providers' compliance to the World Health Organization modified partogram across the active first stage of labor is a graphic representation of a mother's condition that is used as a guide in providing quality obstetrics care. However, little evidence is documented on the health providers' adherence to the use of the partograph in Ethiopia, which limits health care providers' ability to improve quality care services. Therefore, this study assessed the adherence of partograph use and associated factors in Ethiopia. Methods Data from the Ethiopian 2016 National Emergency Obstetric and Newborn Care survey of 3,804 health facilities that provided maternity services were used. We extracted 2611 partograph charts over a 12 months period prior to the survey to review the proper recording of each component. Data analyses were performed using SPSS version 22.0 software. A logistic regression analyses was used to identify the association of explanatory variables with the outcome variable. A p-value of <0.05 was considered as cut off point to declare the significance association in the multivariable analysis. Results Of the total 2611 partographs reviewed, 561(21.5%) of them were fully recorded as per the WHO guideline. Particularly, molding in 50%, color of liquor in 70.5%, fetal heart beat in 93.3%, cervical dilation in 89.6%, descent in 63.2%, uterine contraction in 94.5%, blood pressure in 80.5%, pulse rate in 70.5%, and temperature in 53% were accurately recorded. The odds of adherence to partograph use were 1.4 in rural health facilities when compared to their counterparts (AOR=1.44; 95% CI: 1.15, 1.80, P- 0.002). Conclusion This study revealed a poor level of adherence in partograph use in Ethiopia. Molding, maternal temperature and decent were the least recorded parameters of the partograph. The odds of completion of partograph were high in rural facilities. Strong supporting supervision and mentoring the health workers to better record and use of partograph are needed mainly in urban health facilities. Moreover in the future, interventional research should be conducted to improve the current rate of adherence.